Clostridium autoethanogenum isopropanol production via native plasmid pCA replicon - Nogle, Robert; Nagaraju, Shilpa; Utturkar, Sagar M.; Giannone, Richard J.; Reynoso, Vinicio; Leang, Ching; Hettich, Robert L.; Mitchell, Wayne P.; Simpson, Sean D.; Jewett, Michael C.; Köpke, Michael; Brown, Steven D. (Frontiers in Bioengineering and Biotechnology, 2022)
Clostridium autoethanogenum is a model gas-fermenting acetogen for commercial ethanol production. It is also a platform organism being developed for carbon-negative production of acetone and isopropanol by gas fermentation. We have assembled a 5.5 kb pCA plasmid for type strain DSM10061 (JA1-1) using three genome sequence datasets. pCA is predicted to encode seven open-reading frames and estimated to be a low-copy number plasmid present at approximately 12 copies per chromosome. RNA-seq analyses indicate pCA genes are transcribed at low levels and two proteins, CAETHG_05090 (putative replication protein) and CAETHG_05115 (hypothetical, possible Mob protein) were detected at low levels during batch gas fermentations. Thiolase (thlA), CoA-transferase (ctfAB), acetoacetate decarboxylase (adc) genes were introduced into a vector for isopropanol production in C. autoethanogenum using the native plasmid origin of replication. The availability of the pCA sequence will facilitate studies into its physiological role and could form the basis for genetic tool optimization.